Editorial - Verbeke, Frank (Journal of Health Informatics in Africa, 2024)
On 22 and 23 November, the Burundi Health Informatics Association organized the 2022 HELINA Special Topic Conference “SNCSU 2022, Digital Health Paving the Way to Universal Health Coverage” at the Royal Palace hotel in Bujumbura, focusing on the role of digital health in achieving universal health coverage (UHC) in low-income settings. The main objective of this conference was to share and capitalize on field experiences with digital tools for implementation of UHC in Sub-Saharan Africa.The conference brought together 254 participants from 13 different African countries and 48 of them attended the pre-conference workshops on “Smart glasses and telemedicine for bridging the clinical competence gaps” and “Evaluating digital health project risks and opportunities using social network analysis”. The main conference started with an overview of different national e-health strategies in African countries presented by health experts and authorities from Burundi, DRC, Mali, Senegal, Guinea, Tanzania and Benin. On the first day, parallel sessions hosted presentations on (i) Data warehousing, monitoring and evaluation, (ii) Ontologies and nomenclatures and (iii) Telemedicine.The second day of the conference 3 sessions ran in parallel with contributions on (i) Hospital information management systems, (ii) Clinical decision support, (iii) Education and training in digital health, (iv) E-health enterprise architectures, (v ) demonstrations of real-world UHC solutions and finally (vi) a track with a series of presentations in English (because the main language of the conference was French).A particularly interesting keynote was addressed by the representative of the UNDP project on mental health in Mali (SANDI), more specifically on the use of telemedicine for assisting with mental health issues in remote and security constrained areas.The scientific program of the conference was in the hands of the Institute of Public Health of Burundi and the Digital Health Campus of Lubumbashi, DRC. A total of 49 abstracts, demonstrations and scientific papers were peer-reviewed by 31 reviewers which resulted in the acceptance of 38 presentations of which 2 scientific full papers.The conference strengthened the insight that digital health is pivotal in achieving Universal Health Coverage (UHC), a goal set by the World Health Organization (WHO) to ensure that all individuals and communities receive the health services they need without suffering financial hardship. The integration of digital health technologies can significantly enhance the accessibility, quality, and efficiency of healthcare services, thereby playing a critical role in meeting UHC objectives.First, digital health tools, such as telemedicine and mobile health applications, bridge the gap between healthcare providers and patients, especially in remote and underserved areas. These technologies enable patients to receive consultations, diagnoses, and treatment plans without the need for physical travel, thereby reducing barriers to access.Second, digital health promotes better health outcomes through improved data management and personalized care. Electronic health records (EHRs) ensure that patient data is accurately recorded and easily accessible, facilitating better coordination of care and continuity across different healthcare providers. Additionally, the use of big data and artificial intelligence (AI) in healthcare can lead to more precise and tailored treatments, enhancing the effectiveness of interventions.Furthermore, digital health contributes to cost savings for both healthcare systems and patients. By streamlining administrative processes and reducing the need for unnecessary tests and hospital visits, digital tools can lower healthcare costs. For patients, reduced travel and quicker access to care can also mean less time off work and fewer out-of-pocket expenses.Finally, digital health fosters health education and literacy. Through online platforms and mobile apps, individuals can access reliable health information, empowering them to make informed decisions about their health and wellness.In summary, digital health is essential for achieving UHC as it enhances accessibility, improves quality of care, reduces costs, and empowers individuals with health knowledge. Integrating digital solutions into healthcare systems is a critical step towards ensuring that everyone, everywhere, can obtain the health services they need.